Analisis Terhadap Pengukuran Kompetensi Guru Sekolah Dasar: Analysis of Primary School Teacher Competency Measures - Muh Maulana Sidiq Hasan, La Ode; Achruh, Andi; Rosdiana (ISEDU : Islamic Education Journal, 2023)
This research discusses the Measurement of Teacher Competence, which aims to: 1) knowing the competencies that must be possessed by teachers; 2) knowing how to measure teacher competence; 3) knowing the role of teacher competence in the teaching and learning process. The research method used is the type of library research. The data sources used as research materials are books, journals, and websites that are relevant to the chosen topic. Documentation, especially the search for records, books, papers, articles, journals, and other similar sources as research variables, is a method used to collect data. The results show that to be a good teacher there are 4 competencies that must be possessed, namely pedagogical competence, personality competence, professional competence and social competence. The four competencies must be possessed by a teaching staff or teacher in order to perform their duties and authority optimally, where for PAI teachers there are 2 additional competencies, namely leadership competence and spiritual competence.